First confirmed record of Zu cristatus in the Mediterranean coast of Israel and the eastern shores of the Levant - GOLANI, DANIEL; EDELIST, DOR; MOROV , ARSENIY R.; STERN, NIR (Mediterranean Marine Science, 2023)
In the present paper we report the first substantiated record of the Scalloped ribbonfish Zu cristatus (Bonelli, 1819) from the Mediterranean coast of Israel. The previous unsubstantiated record from Israel was based on a juvenile specimen that was found on the shore over seven decades ago and was not saved. This report constitutes the first confirmed record of this species from the Levant.